2008
DOI: 10.4140/tcp.n.2008.844
|View full text |Cite
|
Sign up to set email alerts
|

Treating Tuberculosis in Older Adults

Abstract: Every second, someone becomes infected with tuberculosis (TB) someplace on Earth. Mycobacterium tuberculosis generally affects the lungs, but can attack any organ. TB occurs along a continuum, and infected individuals may have latent or active TB. In the United States, public health efforts between 1953 and the early 1980s successfully reduced the number of cases. The number began to grow in the 1980s, and several causes were implicated. In the last few years, the number of active TB cases has declined signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Compared with their community-dwelling counterparts, elderly subjects living in long-term-care facilities are at a greater risk for reactivation of latent TB as well as the acquisition of new TB infection. 15,16 Shimouchi et al 17 reported that in nursing homes for elders in Osaka City, Japan, the incidence rate of tuberculosis was 75.2 per 100,000 residents. Another study showed that institutionalized elderly persons had four times more cases than those observed for elderly individuals living at home.…”
Section: Advanced Age As a Risk Factormentioning
confidence: 99%
“…Compared with their community-dwelling counterparts, elderly subjects living in long-term-care facilities are at a greater risk for reactivation of latent TB as well as the acquisition of new TB infection. 15,16 Shimouchi et al 17 reported that in nursing homes for elders in Osaka City, Japan, the incidence rate of tuberculosis was 75.2 per 100,000 residents. Another study showed that institutionalized elderly persons had four times more cases than those observed for elderly individuals living at home.…”
Section: Advanced Age As a Risk Factormentioning
confidence: 99%
“…A recent cross-national study of 62 developing and developed countries reported an increase in suicide rates with aging in males and females in 25 and 27 countries respectively (Shah, 2007). The elderly are at high risk of developing tuberculosis (Trenton and Currier, 2001;Pesut et al, 2008;Zanni and Wick, 2008) and the incidence of tuberculosis in the elderly has increased in recent years (Pesut et al, 2008).…”
Section: Introductionmentioning
confidence: 99%